Redox Cycling of β-Lapachone and Structural Analogues in Microsomal and Cytosol Liver Preparations - Fernandez Villamil, Silvia Hebe (2004)
The lipophilic o-naphthoquinones beta-lapachone and structural analogous quinones (CG quinones) are proposed as cytostatic, trypanocidal and antiviral agents. With rat liver microsomal NAD(P)H cytochrome P450 reductase or cytosol flavoenzyme DTD, these quinones constitute redox systems that in the presence of oxygen generate ROS. o-Naphthoquinones redox cycling, catalyzed by the NADPH cytochrome P450 reductase, generate in microsomal liver preparations: (a) semiquinone free radicals, (b) ROS and (c) inhibition of cytochrome P450-dependent reactions, exerting cytotoxic effects. Hydroquinones, are the immediate products of quinones reduction by the DTD-dependent systems. Three types of hydroquinones formed by that reaction have been proposed by Cadenas: (a) redox stable hydroquinones; (b) redox labile hydroquinones that subsequently reoxidize, with formation of semiquinone and ROS and (c) redox-labile semiquinones that immediately rearrange to potent electrophils undergoing biological alkylating reactions. Our observations with beta-lapachone and related o-naphthoquinones indicate that the corresponding hydroquinones must be included in the second group in agreement with (a) the semiquinone spectrum, demonstrated by ESR spectroscopy; (b) semiquinone (or quinone) production demonstrated by optical spectroscopy and; (c) the effect of dicoumarol on the quinone redox-cycling and oxygen consumption by the NADPH/o-naphthoquinone/DTD system. These reactions associated to DTD activity seem to rule out the contention proposing DTD as an antioxidant enzyme protecting against quinone toxicity.